A preliminary study on the sealing abilities of the intermediate restoratives used in endodontics - Tang, Maria Caridad L.
An in vitro study to determine and compare the sealing abilities of different intermediate restoratives used in Endodontics was conducted using Caviton, Fermin, Ward's Tempak and a "double seal" consisting of an inner layer of Caviton and an outer layer of Ward's Tempak. A 4-mm layer of each material was used to seal access preparations afterwhich the teeth were divided into two groups per material and submerged in 10% methylene blue dye. One group was stored at room temperature while the other was subjected to thermal cycling then the teeth were sectioned and the leakage studied and compared under a stereomicroscope. The most effective material was Caviton, followed by Fermin and the "double seal" and the least effective was the Ward's Tempak.